The Use of Insecticide Mosquito Nets and Insecticide Spraying on the Risk of Malaria in Children: A Meta-Analysis - Arlina Azka; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2021)
Background: Malaria is a vector-borne disease caused by Plasmodium infection and there are more than 30 species of Anopheles which are important vectors of malaria. The main interventions recommended for controlling malaria vectors are the use of insecticide mosquito nets and indoor residual spraying. This study aims to estimate the effect of using insecticide mosquito nets and spraying insecticides on the risk of malaria in children.Subjects and Method: This was a meta-analysis study using PRISMA flow diagram guidelines. Article searches were carried out in the PubMed, Google Scholar, Science Direct, ResearchGate, and SpringerLink databases with the keywords